Blank canvas : my so-called artist's journey. 4 - Higashimura, Akiko; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2020)
"Akiko has finally achieved her dream of becoming a manga artist! She's almost ready to fully immerse herself in the wonderful world of shoujo when Hidaka-sensei approaches her. Just what does he want?"--Provided by publisher.